Three new species of Masdevallia (Orchidaceae: Pleurothallidinae) from the Ayacucho and Puno regions in Peru - Daltröm, Stig; Ruíz Pérez, Saul (Lankesteriana: International Journal on Orchidology, 2015)
Three new species of Masdevallia, subgenus Masdevallia are described, illustrated with line drawings and color photographs, one dwarf species in section Coriaceae and two attractive and rather large species in section Masdevallia. The former section is also treated as the genus Byrsella by Luer (2006). All three new species are distinguished by unique combinations of features that separate them from all other species in the large genus Masdevallia.